The depression and anxiety profiles of motherswho have children with epilepsy - Serin, Hepsen Mine; Akinci, Ayşe; Mermi, Osman; Atmaca, Murat; Yilmaz, Erdal (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2016)
Objective: Epilepsy has important effects to different extents on children and their families. The purpose of the present study was to evaluate the depression and anxiety scores in order to view the psychological profile of mothers of children with epilepsy. Material and Methods: A total of 100 mothers with children having epilepsy were included in the study. The control group consisted of 100 mothers who have children without chronic disease. The Beck depression inventory, the Beck anxiety inventory, the State-Trait anxiety inventory 1 and 2 (STAI 1 ve 2) were used to assess the psychiatric status of the mothers. A statistical software was used to analyze the statistical data. Results: There was no statistical difference between the groups in terms of depression (p=0.285). Anxiety was found in 55% of the mothers who had epileptic children while the rate in the control group was 46%. There was a significant difference between the groups in terms of the mean Beck anxiety scores (p=0.006). There was no statistically significant difference in the mean STAI-1 scores between the groups (p=0.06). There was a significant increase in the mean STAI-2 scores in terms of trait anxiety for the study group compared to the controls (p=0.001). Conclusion: Epilepsy may cause impairment in the quality of life of parents of the affected children. Hence, the awareness of clinicians about the psychosocial consequences for the parents of children with epilepsy may help providing better support and care for such families. © Copyright 2016 by Türkiye Klinikleri.
Keywords: Anxiety; Depression; Epilepsy; Mothers